GAMBARAN PENGETAHUAN DAN PERILAKU LANSIA DENGAN DIABETES MELLITUS TIPE II DI WILAYAH KOTA SEMARANG: DESCRIPTION OF KNOWLEDGE AND BEHAVIOR OF ELDERLY WITH DIABETES MELLITUS TYPE II IN THE CITY OF SEMARANG - Diana Dayaningsih; Yuni Astuti; Nadya Tri Yuwinda; Niken Dwi Rahayu (SEKOLAH TINGGI ILMU KESEHATAN KESDAM IV DIPONEGORO, 2021)
Aging or the process of getting old is a process of disappearing or decreasing health functions in meeting the needs of life. Aging is characterized by sagging skin, gray hair, poor hearing, and worsening vision.1 The WHO classification of elderly (elderly) includes middle age (45-59 years), elderly (60-59 years). 74 years), old (75 – 90 years), very old (above 90 years).2